Desain dan Manufaktur Model Piston Jupiter MX 135 cc Dengan Menggunakan 3D Printer - Wandro Siregar; Parulian Siagian; Richard A.M. Napitupulu (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2020)
A product that will be mass produced requires an initial prototype so that it can assess whether a product design meets the desired criteria and is ready to be mass produced. For the purposes of making the initial prototyping, one alternative is to use 3D printing. Prototyping is an early example of a concept as part of the product development process. Rapid Prototyping allows the visualization of a 3D (three-dimension) image into an original three-dimensional object that has a volume. In addition, rapid prototyping products can also be used to test certain parts. In the design process the 2017 Solidworks software and manufacturing process are used anet type 3D printer. In the manufacturing process many 3D Printer parameters must be regulated and very influential on the manufacturing results to be obtained, including the 3D printer parameter settings in the slicing process. This is a process that is very influential on the results, where the process of slicing the material temperature, printing speed, wall thickness, layer thickness and support must be set properly. In the future it is expected that research on 3D printing manufacturing results with the same printer parameters for the design results of some CAD software.